Giant pedunculated oesophageal liposarcomas: A review of literature and resection techniques - Ng, Y. Annalisa (Int J Surg Case Rep, 2019)
INTRODUCTION AND PRESENTATION OF CASE: Liposarcomas are rare causes of oesophageal tumours, accounting for <1% of tumours. We present a case of a dedifferentiated oesophageal liposarcoma arising from a giant fibrovascular polyp for which resection was performed via a left cervical oesophagostomy with transgastric retrieval of tumour. We also review the existing literature focusing on discussion of resection techniques. DISCUSSION: To date, 62 cases of oesophageal liposarcoma have been reported in the literature. They usually occur in males (74.2%), with a median age of 66 years (range 38–84 years). Such tumours present most commonly with dysphagia (69.4%); usually arise from the cervical oesophagus (79%), and are well-differentiated. Treatment options include surgery and recently, endoscopic resection techniques such as submucosal dissection (ESD). CONCLUSION: Giant oesophageal liposarcomas are very rare tumours. Such tumours are usually polypoid, arising from a pedicle. As such, resection techniques have shifted away from oesophagectomy to less invasive means such as endoscopic resection or oesophagostomy. Decision on type of resection technique depends on tumour characteristics and location; with the guiding principle being resection with clear margins in order to prevent local recurrence.